2022
DOI: 10.1007/s00268-022-06859-5
|View full text |Cite
|
Sign up to set email alerts
|

Preperitoneal Packing for Pelvic Fracture Bleeding Control: A Human Cadaver Study

Abstract: Background Preperitoneal packing (PPP) has been widely accepted as a damage control technique for severe bleeding from pelvic fractures. It is supposed to work by direct compression and tamponade of the bleeding source in the pelvis and it has been suggested to be effective for both venous and arterial bleeding. However, there is little evidence to support its efficacy or the ability to place the laparotomy pads in proximity of the desired location. Methods Bilateral PPP was performed on 10 fresh human cadaver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Thank you to Drs. Bagaria, Rani, and Gora for their comments regarding our article, “Preperitoneal Packing for Pelvic Fracture Bleeding Control: A Human Cadaver Study” [1]. Certainly, we agree with your concerns of generalizing these data too immediately to clinical practice, but we feel it is important to highlight the potential weaknesses of the discussed intervention.…”
mentioning
confidence: 95%
“…Thank you to Drs. Bagaria, Rani, and Gora for their comments regarding our article, “Preperitoneal Packing for Pelvic Fracture Bleeding Control: A Human Cadaver Study” [1]. Certainly, we agree with your concerns of generalizing these data too immediately to clinical practice, but we feel it is important to highlight the potential weaknesses of the discussed intervention.…”
mentioning
confidence: 95%
“…A recent publication by Benjamin et al in the World Journal of Surgery captivated our attention immensely [1]. In their publication, the authors performed an experimental study assessing preperitoneal packing (PPP) efficacy by manually measuring pack distance with important anatomical landmarks in noninjured fresh human cadavers and concluded that considering the noncontact placement of packs, the role of PPP needs to be revisited in pelvic hemorrhage management.…”
mentioning
confidence: 99%